2021
DOI: 10.1007/s00011-021-01498-3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF-1 signaling promotes immunosuppression via the STAT3 pathway: impact on the aging process and age-related diseases

Abstract: Background The insulin/IGF-1 signaling pathway has a major role in the regulation of longevity both in Caenorhabditis elegans and mammalian species, i.e., reduced activity of this pathway extends lifespan, whereas increased activity accelerates the aging process. The insulin/IGF-1 pathway controls protein and energy metabolism as well as the proliferation and differentiation of insulin/IGF-1-responsive cells. Insulin/IGF-1 signaling also regulates the functions of the innate and adaptive immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 175 publications
(241 reference statements)
1
27
0
1
Order By: Relevance
“…Our results showed that OSM stimulation for 24 h increased both the total STAT3 and phosphorylated STAT3 levels in the cervical cancer cell lines (HeLaS3 and SiHa). In contrast, previous studies reported that short-term exposure to OSM showed a reduction or maintenance pattern of STAT3 through negative feedback mediated by SOCS3 [ 68 , 69 ]. In our case, SD-36, a STAT3-specific degrader, reduces total STAT3 and STAT3 phosphorylation at Ser727.…”
Section: Discussionmentioning
confidence: 80%
“…Our results showed that OSM stimulation for 24 h increased both the total STAT3 and phosphorylated STAT3 levels in the cervical cancer cell lines (HeLaS3 and SiHa). In contrast, previous studies reported that short-term exposure to OSM showed a reduction or maintenance pattern of STAT3 through negative feedback mediated by SOCS3 [ 68 , 69 ]. In our case, SD-36, a STAT3-specific degrader, reduces total STAT3 and STAT3 phosphorylation at Ser727.…”
Section: Discussionmentioning
confidence: 80%
“…As many factors that regulate aging and immunity are evolutionarily conserved from C. elegans to mammals, factors and pathways discussed here may also regulate immunosenescence in humans. Consistent with this possibility, p38 MAPK and insulin/IGF-1 signaling contributes to immunosenescence in mammals [5,45]. Thus, further research is required to unravel the molecular mechanism of immunosenescence in humans to improve treatment therapy of age-related pathologies.…”
Section: Discussionmentioning
confidence: 87%
“…The insulin signaling pathway has been widely investigated in fat metabolism [ 26 ]. After insulin binds to the extracellular alpha subunit of the insulin receptor (InsR), it activates tyrosine kinase activity of the intracellular beta subunit, and the beta subunit undergoes autophosphorylation so that the tyrosine of the downstream substrate is phosphorylated and activated [ 27 ]. Insulin promotes the synthesis of fat and glycogen by acting on target tissues and inhibits the decomposition rate of lipids and liver glycogen, strongly promoting the storage of substances in the body.…”
Section: Discussionmentioning
confidence: 99%